Kiss me in the Coral Lounge [large type] : intimate confessions from a happy marriage - Ellis, Helen (Random House, 2023)
"Welcome to the Coral Lounge, a room in Helen Ellis's New York City apartment painted such an exuberant shade of Sherman Williams that a peeping Tom once left a sticky note with the doorman asking for the color. It is in the Coral Lounge that the magic of Helen's marriage unfolds: Shindigs where strangers swap clothing in the powder room, a party game called "What's in the box?" makes its uproarious debut, the Puzzle Posse pounces on a 500-piece jigsaw of a beheaded priest. Then, when the pandemic shuts down the city, the Coral Lounge becomes a place of refuge, where Helen and her husband eat take-out while sitting on the floor like toddlers, dragging French fries through a ketchup swamp, where they sing to the two enormous cats who chew on Helen's hair while she sleeps, and where they while away the hours with Mexican Viagra and the ensuing neck injury. In these surprising, romantic, sexy, and hilariously frank essays Helen Ellis paints a portrait of true romance for our times"--